1999
DOI: 10.1902/jop.1999.70.5.490
|View full text |Cite
|
Sign up to set email alerts
|

Two Multi‐Center Studies Evaluating Locally Delivered Doxycycline Hyclate, Placebo Control, Oral Hygiene, and Scaling and Root Planing in the Treatment of Periodontitis

Abstract: Results of this trial demonstrate that treatment of periodontitis with subgingivally delivered doxycycline in a biodegradable polymer is equally effective as scaling and root planing and superior in effect to placebo control and oral hygiene in reducing the clinical signs of adult periodontitis over a 9-month period. This represents positive changes resulting from the use of subgingivally applied doxycycline as scaling and root planing was not limited regarding time of the procedure or use of local anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(152 citation statements)
references
References 29 publications
4
131
1
4
Order By: Relevance
“…These conclusions are supported by several clinical studies that could prove the efficacy of locally administered doxycycline in terms of gain of attachment [13,40,41]. In two multicenter clinical trials designed to study the efficacy of a doxycycline containing drug delivery system, a reduction of PD of 1.3 mm and clinical attachment gain of 0.8 mm were obtained at month 9 [40]. Our results confirm the high inter-individual variability of concentration in GCF after local delivery of doxycycline observed by other authors [12].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These conclusions are supported by several clinical studies that could prove the efficacy of locally administered doxycycline in terms of gain of attachment [13,40,41]. In two multicenter clinical trials designed to study the efficacy of a doxycycline containing drug delivery system, a reduction of PD of 1.3 mm and clinical attachment gain of 0.8 mm were obtained at month 9 [40]. Our results confirm the high inter-individual variability of concentration in GCF after local delivery of doxycycline observed by other authors [12].…”
Section: Discussionmentioning
confidence: 62%
“…Although this available drug concentration in the carrier is lower than that of tetracycline HCl used at 25% loading in tetracyline fibers (Actisite † ), the MIC of doxycycline for suspected periodontal pathogens was exceeded for at least 10 days after application of the gel. These conclusions are supported by several clinical studies that could prove the efficacy of locally administered doxycycline in terms of gain of attachment [13,40,41]. In two multicenter clinical trials designed to study the efficacy of a doxycycline containing drug delivery system, a reduction of PD of 1.3 mm and clinical attachment gain of 0.8 mm were obtained at month 9 [40].…”
Section: Discussionmentioning
confidence: 67%
“…Thus, high concentrations of antimicrobial agents are needed before a beneficial effect can be expected. Gingival crevicular fluid (GCF) concentrations to peak with a concentration of 1473-1986 mg/ml at 2 hours and gradually decreased to 309 mg/ml at the end of 7 days which was above the minimum inhibiting concentration for doxycycline [17]. Several studies comparing SRP with doxycycline local gels have revealed similar results, which indicates either SRP or doxycycline gel alone may be favorable [18].…”
Section: In-vitro Release Studies Of Doxmentioning
confidence: 95%
“…Initial studies demonstrated that doxycycline was the most potent tetracycline in inhibition of collagenolytic activities (Burns, et al, 1989). This property of doxycycline provided the pharmacological rationale for the use of a low or subantimicrobial dose of doxycycline (SDD) that was shown to be efficient in inhibiting mammalian collagenase activity without developing antibiotic resistance (Golub, et al, 1990). Several clinical studies have been conducted assessing the benefits of the SDD as an adjunctive therapy to scaling and root planing (SRP) in the treatment of the periodontal disease.…”
Section: Mmp Inhibitorsmentioning
confidence: 99%